Tuberculosis Among Native Hawaiian and Other Pacific Islander Persons: United States and U.S.-Affiliated Pacific Islands, 2010?2019 (Mary Ann Liebert, 2022)
Background: In recent years, tuberculosis (TB) incidence in the United States has declined overall but remained high among Native Hawaiian and Other Pacific Islander (NH/PI) persons. Few studies have examined the epidemiology of TB among NH/PI persons, particularly in the U.S.-Affiliated Pacific Islands (USAPI). We describe TB incidence and characteristics of NH/PI patients during 2010?2019. Methods: We used data from the National Tuberculosis Surveillance System to characterize TB cases reported among NH/PI persons born in the 50 U.S. states (defined to include District of Columbia) and the USAPI. We calculated annual TB incidence among NH/PI patients, stratified by place of birth (U.S. states or USAPI). Using Asian persons born outside the United States?persons historically grouped with NH/PI persons as one racial category?as the reference, we compared demographic, clinical, and socio-behavioral characteristics of NH/PI TB patients. Results: During 2010?2019, 4359 TB cases were reported among NH/PI patients born in the U.S. states (n=205) or the USAPI (n=4154). Median annual incidence per 100,000 persons was 6.5 cases (persons born in the U.S. states) and 150.7 cases (persons born in the USAPI). The proportion of TB patients aged <15 years was higher among NH/PI persons (U.S. states: 54%, USAPI: 24%) than among Asian persons born outside the United States (1%). Conclusions: TB incidence among NH/PI persons is high, particularly among persons born in the USAPI, emphasizing the need to enhance TB prevention strategies in these communities. Interventions should be tailored toward those who experience the highest risk, including NH/PI children and adolescents.